2005
DOI: 10.1016/j.ijgo.2005.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐hydroxybutyrate dehydrogenase activity in intrahepatic cholestasis of pregnancy

Abstract: Alpha-hydroxybutyrate dehydrogenase serum activity seems to be another biochemical parameter useful in the assessment of ICP severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…HBDH is an isoenzyme of LDH exhibiting LDH activity. Previous studies have shown that HBDH can be used to assess the severity of systemic lupus erythematosus-associated liver injury diseases, intrahepatic cholestasis of pregnancy and AIDS-related pneumocystis pneumonia [22][23][24]. All these studies indicate the importance of serum HBDH as a clinical biomarker.…”
Section: Discussionmentioning
confidence: 94%
“…HBDH is an isoenzyme of LDH exhibiting LDH activity. Previous studies have shown that HBDH can be used to assess the severity of systemic lupus erythematosus-associated liver injury diseases, intrahepatic cholestasis of pregnancy and AIDS-related pneumocystis pneumonia [22][23][24]. All these studies indicate the importance of serum HBDH as a clinical biomarker.…”
Section: Discussionmentioning
confidence: 94%
“…α-HB is an organic acid formed by α-HB dehydrogenase that catalyzes the reduction of α-ketobutyric acid to α-HB (16). A ketobutyrate is a product of conversion of cystathionine to cysteine, which results in increased antioxidants, including glutathione production.…”
Section: Discussionmentioning
confidence: 99%
“…HBDH is an isoenzyme of LDH and exhibits LDH activity. Previous studies have shown that HBDH can be used to assess the severity of systemic lupus erythematosus-associated liver injury diseases, intrahepatic cholestasis of pregnancy and AIDS-related pneumocystis pneumonia [22][23][24] . All these studies indicate the possibility of serum HBDH in clinical practice.…”
Section: Correlation Between Serum Hbdh Levels and Other Clinical Indmentioning
confidence: 99%